Influencia de las estrategias lúdicas en el desarrollo de destreza gruesas y finas en los niños y las niñas de educación inicial de la Unidad Educativa Particular Bilingϋe Paraíso de los Niños de la ciudad de Machala, provincia de El Oro, durante periodo lectivo 2011-2012. - Hernández Abad, Sandy Beatriz (2013)
The subject treated in this research work concerns the influence of playful strategies in developing gross and fine children's skills and girls Early Childhood Education of the Special Education Unit Bilingϋe, Children's Paradise, the city of Machala it is therefore in the components of the development of the thesis explains each of the content raised by the policies of the university, so much detail are considered the issues concerning the ludic Strategies to develop gross motor skills and fine of students.